Analisis Gerakan Literasi Sekolah di Sekolah Dasar - Mariyah Ulpah; Laelia Nurpratiwiningsih; Moh. Toharudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The School Literacy Movement is carried out with the aim of cultivating the character of students through the cultivation of a school literacy ecosystem in order to make students have a high reading culture and writing skills. Based on this, the problem in this research is how to implement the school literacy movement at SDN 03 Tegalglagah and what are the supporting and inhibiting factors in the school literacy movement at SDN 03 Tegalglagah. This research method uses descriptive qualitative research with a case study approach. Data collection techniques in this study are using observation, interviews, and documentation. The results of this study can be concluded that the implementation of the School Literacy Movement is adjusted to the curriculum and follows government programs as well as contributions with parents so that students are accustomed to reading at home, and provide facilities and infrastructure to support the implementation of the school literacy movement at SDN 03 Tegalglagah, the application of GLS itself is carried out in each subject. At the implementation stage of the school literacy movement at SDN 03 Tegalglagah through three stages, namely, the implementation stage, the development stage, and the learning stage.